2023
DOI: 10.3390/agriculture13010225
|View full text |Cite
|
Sign up to set email alerts
|

Crop Yield Prediction Using Machine Learning Models: Case of Irish Potato and Maize

Abstract: Although agriculture remains the dominant economic activity in many countries around the world, in recent years this sector has continued to be negatively impacted by climate change leading to food insecurities. This is so because extreme weather conditions induced by climate change are detrimental to most crops and affect the expected quantity of agricultural production. Although there is no way to fully mitigate these natural phenomena, it could be much better if there is information known earlier about the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 30 publications
0
37
0
7
Order By: Relevance
“…In Rwanda, for example, farmers opt for crops such as bananas and cassava, which are well suited to warm, humid climates (Moniruzzaman, 2015). Climate is pivotal in determining crop suitability for cultivation, authors highlight the effects of climate change on agriculture necessitate farmers' adaptation to mitigate these effects (Mikova et al, 2015) Most agricultural activities revolve around seasonal characteristics, leading farmers to choose crops based on available rainfall, as different crops have varying water needs (Kuradusenge et al, 2023).…”
Section: Factors Influencing the Choice Of Cropsmentioning
confidence: 99%
“…In Rwanda, for example, farmers opt for crops such as bananas and cassava, which are well suited to warm, humid climates (Moniruzzaman, 2015). Climate is pivotal in determining crop suitability for cultivation, authors highlight the effects of climate change on agriculture necessitate farmers' adaptation to mitigate these effects (Mikova et al, 2015) Most agricultural activities revolve around seasonal characteristics, leading farmers to choose crops based on available rainfall, as different crops have varying water needs (Kuradusenge et al, 2023).…”
Section: Factors Influencing the Choice Of Cropsmentioning
confidence: 99%
“…Hahn et al, (2023) [21] evaluated the effects of nitrogen fertilization, orchards, and cultivars on predicting yields of 'Royal Gala' and 'Fuji Suprema' apples in a subtropical climate. In a study conducted by Kuradusenge et al (2023) [22], crop harvest estimations were made utilizing historical weather data and yield information through various ML techniques. The researchers observed that the Random Forest (RF) model exhibited superior accuracy in forecasting crop yield in comparison to other ML methods.…”
Section: B Yield Estimation Techniques Based On Metrological (Climate...mentioning
confidence: 99%
“…𝑊 represents the connection weight between the jth hidden neuron and the kth output neuron. (𝑏 ) denotes the bias for the To assess the performance of the ANN model, the coefficient of determination (R 2 ), root mean square error (RMSE), and mean absolute error (MAE) were used as evaluation metrics [41,42]. These parameters were calculated using Equations ( 11)-( 13):…”
Section: Neural Network Modelling Of Specific Energy Requirementsmentioning
confidence: 99%